DOLMEN ORANG MALUKU: EKSISTENSI RELIGI, ADAT DAN INTEGRASI SOSIAL (Tinjauan Etnoarkeologi) - Wuri Handoko (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2009)
Dolmen for the Moluccans is a symbol of their ancestor’s rites which up until now is remained functioned. Today every person in the village uses dolmen as a medium for their rites. While the community as a whole use dolmen as a medium for traditional ceremony such as king accession and other ceremonies. An Ethnoarchaeological approach is used to identify the meaning and function of dolmen for today’s community as an interpretation for the past.